2013
DOI: 10.4172/2155-9600.1000226
|View full text |Cite
|
Sign up to set email alerts
|

Ginger Protects the Liver against the Toxic Effects of Xenobiotic Compounds: Preclinical Observations

Abstract: According to the World Health Organization, chronic liver disease is a major ailment and causes significant morbidity and mortality in both western and developing countries. However, till date no ideal hepatoprotective agents are available in the modern system of medicine to effective prevent and cure liver ailments. This has necessitated the need to depend on complementary and alternative systems of medicine for liver ailments and diseases. Zingiber officinale Roscoe commonly known as ginger is arguably one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 47 publications
2
2
0
Order By: Relevance
“…The observed phenomenon may be attributed to the anti-cancer action of Gin/Sor, which mitigates liver damage. Several further investigations have corroborated our results, demonstrating agreement that the concurrent administration of Sor and Gin may effectively reduce blood levels of ALT, AST, ALP, and bilirubin [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 83%
“…The observed phenomenon may be attributed to the anti-cancer action of Gin/Sor, which mitigates liver damage. Several further investigations have corroborated our results, demonstrating agreement that the concurrent administration of Sor and Gin may effectively reduce blood levels of ALT, AST, ALP, and bilirubin [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 83%
“…Treatment with ginger extract and GNPs in the different experimental groups increased the activity of the hepatic tissue CAT significantly as compared to the infected non treated mice group (G2) (P < 0.001), which is in agreement with many researches, which have also shown that ginger enhances the level of antioxidant enzyme [8,35,36,37] In the present study, the level of MDA, lipid peroxidation end product, was notably elevated in the liver of the positive control mice group (G2). This elevated MDA level indicates strong lipid peroxidation with a failure of the host antioxidant defense mechanisms to prevent excessive free radical formation and tissue damage [38,39].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 88%
“…The underground rhizomes of ginger are the medicinally useful part [11]. Many studies were carried out on the pungent constituents of fresh and dried ginger rhizomes [13]. Among the pharmacological effects demonstrated are anti-platelets, antioxidant, anti-tumor, anti-rhino viral, hepatoprotective, anti-arthritic and anti-inflammatory [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a worldwide trend to go back to traditional medicinal plants. Many natural products of herbal origin are in use for the treatment of liver aliments [13]. Zingiber officinale (ginger) is gaining popularity among modern physicians.…”
Section: Introductionmentioning
confidence: 99%